First demonstration of high current canted-cosine-theta coils with Bi-2212 Rutherford cables. (8th January 2021) - Garcia Fajardo, L; Shen, T; Wang, X; Myers, C; Arbelaez, D; Bosque, E; Brouwer, L; Caspi, S; English, L; Gourlay, S; Hafalia, A; Martchevskii, M; et al.
Abstract: Future high energy physics colliders could benefit from accelerator magnets based on high-temperature superconductors, which may reach magnetic fields of up to 45 T at 4.2 K, twice the field limit of the two Nb-based superconductors. Bi2 Sr2 CaCu2 O8-x (Bi-2212) is the only high- T c cuprate material available as a twisted, multifilamentary and isotropic round wire. However, it has been hitherto unclear how an accelerator magnet can be fabricated from Bi-2212 round wires and whether high field quality can be achieved. This paper reports on the first demonstration of high current Bi-2212 coils using Rutherford cable based on a canted-cosine-theta (CCT) design and an overpressure processing heat treatment. Two Bi-2212 CCT coils, BIN5a and BIN5b, were made from a nine-strand Rutherford cable. Their electromagnetic design is identical, but they were fabricated differently: both coils underwent heat treatment in their aluminum–bronze mandrels, but unlike BIN5a that was impregnated with epoxy in its reaction mandrel, the conductor of BIN5b was transferred to a 3D printed Accura Bluestone mandrel after the heat treatment, a process attempted here for the first time, and was not impregnated. BIN5a reached a peak current of 4.1 kA with a self-field of 1.34 T in the bore. This corresponds to a wire engineering current density ( J e ) of 912 A mm −2, which is two times that of BIN2-IL, a previous Bi-2212 CCT coil fabricated at LBNL, which used a six-around-one cable processed with the conventional 1 bar pressure melt processing. On the other hand, BIN5b reached 3.1 kA. The coils exhibited no quench training. All the quenches were thermal runaways that occurred at the same location. In addition, we report on the field quality and ramp-dependent hysteresis measurements taken during the test of BIN5a at 4.2 K. Overall, our results demonstrate that the CCT technology is a route that should be further investigated for making high field, potentially quench training free dipole magnets with Bi-2212 cables.